Struktur dan Fungsi Sosial Cerita Rakyat Legenda Syekh Muhammad Yatim Tuangku Ampalu di Nagari Tandikek Kecamatan Patamuan Kabupaten Padang Pariaman - Yozi Alta Pranata; Hasanuddin WS Hasanuddin WS (Persona: Kajian Bahasa dan Sastra, 2022)
This study aims to describe: first the structure of the folklore of the legend of Sheikh Muhammad Yatim Tuangku Ampalu, second) the social function of the folklore of the legend of Sheikh Muhammad Yatim Tuangku Ampalu in Nagari Tandikek, Patamuan District, Padang Pariaman Regency. This type of research is a qualitative research using descriptive method. The data in this study are the data in this study is the folklore of the legend of Sheikh Muhammad Yatim Tuangku Ampalu in Nagari Tandikek, Patamuan District, Padang Pariaman Regency. The data collected in this study were then analyzed with the following steps: (1) data identification stage, (2) data classification or analysis stage, (3) data discussion or conclusion stage, (4) reporting stage. There are two findings in this study. First, the structure of the legend of Sheikh Muhammad Yatim Tuangku Ampalu is divided into six, namely language style, characters and characterizations, plot and plot, setting, theme, and message. Second, the social function of the legend of Sheikh Muhammad Yatim Tuangku Ampalu is divided into three, namely educating, inheriting, and identity. Based on these findings, it turns out that folklore in the form of legends is still an oral literature that is highly trusted by the local community to this day.